Enhancer architecture-dependent multilayered transcriptional regulation orchestrates RA signaling-induced early lineage differentiation of ESCs. Issue 20 (1st November 2021) - Su, Guangsong; Wang, Wenbin; Zhao, Xueyuan; Chen, Jun; Zheng, Jian; Liu, Man; Bi, Jinfang; Guo, Dianhao; Chen, Bohan; Zhao, Zhongfang; Shi, Jiandang; Zhang, Lei; et al.
Abstract: Signaling pathway-driven target gene transcription is critical for fate determination of embryonic stem cells (ESCs), but enhancer-dependent transcriptional regulation in these processes remains poorly understood. Here, we report enhancer architecture-dependent multilayered transcriptional regulation at the Halr1–Hoxa1 locus that orchestrates retinoic acid (RA) signaling-induced early lineage differentiation of ESCs. We show that both homeobox A1 ( Hoxa1) and Hoxa adjacent long non-coding RNA 1 ( Halr1 ) are identified as direct downstream targets of RA signaling and regulated by RARA/RXRA via RA response elements (RAREs). Chromosome conformation capture-based screens indicate that RA signaling promotes enhancer interactions essential for Hoxa1 and Halr1 expression and mesendoderm differentiation of ESCs. Furthermore, the results also show that HOXA1 promotes expression of Halr1 through binding to enhancer; conversely, loss of Halr1 enhances interaction between Hoxa1 chromatin and four distal enhancers but weakens interaction with chromatin inside the HoxA cluster, leading to RA signaling-induced Hoxa1 overactivation and enhanced endoderm differentiation. These findings reveal complex transcriptional regulation involving synergistic regulation by enhancers, transcription factors and lncRNA. This work provides new insight into intrinsic molecular mechanisms underlying ESC fate determination during RA signaling-induced early differentiation. Graphical Abstract: